Prevalence Of Parasites In Freshwater Fishes In The Southern Part Of Ligawasan Marsh, Philippines - Sarip Tarita Ampatuan Ali (Procedia of Social Sciences and Humanities, 2021)
Ligawasan Marsh, the largest river basin in Mindanao is home of common fishes such as dalag, pupuyo, hito, tilapia and gourami. Fish parasites pose a great threat to freshwater fishes to public health and economy of an area. This study aims to examine the Prevalence of Parasites in Freshwater Fishes in the Southern Part of Ligawasan Marsh; Endoparasites in the representative species; Mean intensity and abundance infection of the Endoparaites. The study utilized necropsy, dissection and microscopy method to examine Endoparasites. Trematodes Clinostomum sp, suspected Camallanus sp., a Neocamallanus sp. and a member of Order Spirurida, all nematodes were recovered. The study yielded that Fish parasites in Channa striata Anabas testudineus had prevalence in Kabuntalan and Datu Piang. Nine Acanthocephalan recovered in Oreochromis niloticus had also prevalence rate. Suspected trematode cysts and eggs were also recovered in Trichopodus trichopterus and Clarias macrocephalus. Thus, it is concluded that there is prevalence of nematodes and trematodes species in C. striata, A. testudineus, O. niloticus, C. macrocephalus and T. trichopterus The Camallanus sp and Neocamallanus sp, both common aquarium parasites are first found in the Southern part of Ligawasan Marsh.